Symbolic Interpretation of Prophet Moses’ Sandals in QS. Ṭāhā [20]:12: A Semiotic Analysis Based on Charles Sanders Peirce’s Theory - Syifa Syifa; Desi Erawati; Nor Faridatunnisa (Palita: Journal of Social Religion Research, 2026)
The Qur’an contains many symbolic narratives, necessitating a reading that goes beyond the literal and requires an interpretive unpacking of meaning. This study is motivated by the importance of understanding the Qur’an in an open-minded manner. This research is a qualitative library study. The method employs descriptive-analytical analysis using sources from classical exegesis, contemporary exegesis, and other relevant books. The data will be analyzed through Charles Sanders Peirce’s triadic semiotic framework. The research findings indicate that sandals are not merely interpreted as footwear but as a symbol of humanity’s connection to the profane world. From the semiotic analysis, the sandal as a representament reflects the human condition of Prophet Moses; as an object, it points to worldly attachment; and as an interpretant, it gives rise to a spiritual meaning: the necessity for Moses to purify himself before entering the sacred space, namely the Valley of Tuwa. The command fa-khla‘ na‘layka (فَاخْلَعْ نَعْلَيْكَ) is interpreted as a symbol of existential transformation toward a servant’s readiness to receive revelation. Therefore, this research contributes to the development of semiotic-based interpretation and can provide implications that sacredness is not enough to be realized only through external symbols, but through inner awareness, reverence when facing God which is likened to wearing a mukena for a woman.